YouTube Videos Support Descriptive Writing Skills in Junior High School - Amalia, Rahma; Santoso, Dian Rahma (Indonesian Journal of Education Methods Development, 2025)
General Background: Writing is a fundamental skill in English language learning, yet it poses persistent challenges for students, particularly in constructing descriptive texts. Specific Background: The integration of digital media, such as YouTube, offers a potential solution to enhance writing instruction by providing engaging and accessible content. Knowledge Gap: However, there remains limited empirical evidence on the effectiveness of YouTube as a medium for improving descriptive writing skills among junior high school students. Aims: This study aims to investigate the impact of YouTube video content on students’ ability to write descriptive texts. Results: Utilizing a quantitative pre-experimental design involving a pre-test and post-test, the study revealed a significant improvement in students’ writing performance. The post-test average score (88.6) exceeded the pre-test score (78.6), and the t-test result (-10.247 > 2.085) confirmed the statistical significance of this difference. Novelty: This study contributes novel insights into the use of the “Easy English” YouTube channel as a practical instructional tool specifically targeted at enhancing descriptive text writing. Implications: The findings suggest that YouTube can be effectively incorporated into English language pedagogy to improve students' writing abilities, thereby supporting the development of media-enriched learning environments at the junior high school level. Highlights :  YouTube enhances students’ descriptive writing performance. Pre-experimental design shows significant score improvement. Digital media supports engaging English instruction. Keywords : YouTube, Descriptive Text, Writing Skills, Junior High School, Language Learning